2017
DOI: 10.5262/tndt.2017.1003.19
|View full text |Cite
|
Sign up to set email alerts
|

Tikagrelor Kullanımı Atorvastatin İlişkili Rabdomiyoliz Riskini Artırabilir

Abstract: ÖZTikagrelor, akut koroner sendrom sonrasında kullanılan antiplatelet agregasyon inhibitörüdür. Statinler gibi karaciğerde sitokrom P450 enzim sistemi ile metabolize olmaktadır. Bu nedenle tikagrelor, atorvastatinin kan düzeyini artırarak statin ilişki rabdomiyolize neden olabilmektedir. Tikagrelorun son dönemde kullanımı giderek arttığından dolayı rabdomiyoliz yan etkisi de görülmektedir. Tikagrelor kullanan bir hastada, muhtemel atorvastatin düzeyinin artması sonucu gelişen şiddetli rabdomiyoliz olgusu sunac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A review of literature revealed eleven [14][15][16][17][18][19][20][21][22][23][24] reported cases of ticagrelor induced ARF and rhabdomyolysis (Table 1). 10 cases were found in patients who were also on prescription of high intensity statins with rosuvastatin being the most commonly used statin.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature revealed eleven [14][15][16][17][18][19][20][21][22][23][24] reported cases of ticagrelor induced ARF and rhabdomyolysis (Table 1). 10 cases were found in patients who were also on prescription of high intensity statins with rosuvastatin being the most commonly used statin.…”
Section: Discussionmentioning
confidence: 99%
“…The statin drugs have a welldocumented association with rhabdomyolysis. [5][6][7][8][9][10][11][12][13][14][15][16] Known risk factors for statin-induced myopathies include higher statin potency, increased statin blood concentrations (through inhibition of metabolism or reduced renal clearance), age greater than 75 years, female gender, and low BMI. 17 While the mechanism by which statins cause this disorder is poorly understood, it is known that they are metabolized by various isoforms of the cytochrome P450 (CYP) enzymes, and inhibition of these enzymes can lead to statin accumulation and increased risk of myopathies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Several case reports have shown the development of rhabdomyolysis and acute renal failure in patients receiving this drug combination. [5][6][7][8][9][10][11][12][13][14][15] This article presents a unique case in which Ms. Y, a 72-year-old female without prior kidney disease, developed rhabdomyolysis and acute kidney injury after being on ticagrelor and rosuvastatin for 4 months without concomitant angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs).…”
mentioning
confidence: 99%